Correlation between Surface Reactions and Electrochemical Performance of Al2O3‐ and CeO2‐Coated NCM Thin Film Cathodes. Issue 9 (17th February 2023) - Hemmelmann, Hendrik; Ruess, Raffael; Klement, Philip; Schörmann, Jörg; Chatterjee, Sangam; Sann, Joachim; Elm, Matthias T.
Abstract: Depositing ultrathin oxide coatings has been proven a successful approach to stabilize the surface of LiNi x Co y Mn z O2 active cathode material in lithium‐ion batteries (LIB). The beneficial effect of Al2 O3 coatings arises at least partly from spontaneous reactions between coating and liquid electrolyte. However, it remains unclear if comparable surface reactions occur for other oxide coatings. One difficulty is the characterization of reaction products at the cathode–electrolyte interface due to the multi‐phase properties of composite cathodes. Here, thin films are utilized as model systems to correlate surface reactions with the performance of Al2 O3 ‐ and CeO2 ‐coated nickel cobalt manganese oxides (NCM). Electrochemical characterization confirms that an Al2 O3 coating improves long‐term cycling stability, while CeO2 ‐coated thin films perform even worse than uncoated counterparts. The analysis of the surface reaction products using X‐ray photoelectron spectroscopy shows that both coatings are fluorinated upon contact with liquid electrolyte in agreement with thermodynamic considerations. The fluorinated Al2 O3 coating is stable during cycling, resulting in the improved cell performance. In contrast, the fluorinated CeO2 coating changes chemical composition, facilitating corrosion of the NCM surface. The results demonstrate the importance of a detailed analysis of surface reactions to evaluate the suitability of ultrathin oxide layers as protective coatings for LIBs. Abstract : Comparing the electrochemical performance of coated NCM111 thin film cathodes shows that Al2 O3 is more suitable as protective coating than CeO2 . Surface analysis using X‐ray photoelectron spectroscopy reveals that both coatings get fluorinated in contact with liquid electrolyte. While fluorinated Al2 O3 is stable during cycling, the fluorinated CeO2 coating changes composition giving rise to a more pronounced capacity fading.